Implementasi Program Jogo Tonggo dalam Penanganan Covid-19 di Provinsi Jawa Tengah - Dinda Permata Putri; Budi Puspo Priyadi; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
The World Health Organization (WHO) declared Covid-19 a global pandemic because it has spread widely in the world. The impact is felt not only in the health sector but also in other fields such as the economy, socio-culture, and education, to influencing government policies. In Indonesia, the implementation of the Large-Scale Social Restriction (PSBB) policy has been carried out to prevent the spread of Covid-19 in several areas such as DKI Jakarta and Surabaya. In contrast to Central Java Province, which implemented the Jogo Tonggo policy, a community-based policy at the Residents' House (RW) level in an effort to deal with Covid-19 that requires collaboration between the government and the community. This study uses descriptive qualitative research methods. Data collection is done through literature study and documentation. The results showed that Jogo Tonggo during the Covid-19 emergency period encouraged the formation of joint awareness and obedience of the citizens of Central Java to the government's appeal. Community obedience is driven by choices, namely: obeying because of the threat of a pandemic, strengthening social solidarity and human values, togetherness in society at the RT and RW levels, as well as the existence of legal rules that contain sanctions.